Managing Their Own Affairs : The Australian Deaf Community in the 1920s and 1930s - Carty, Breda (Book collections on Project MUSE., 2018)
Managing Their Own Affairs explores how Deaf organizations and institutions were forged in Australia during the early 20th century. During this period, deaf people challenged the authority of the dominant welfare organizations, or Deaf Societies, which were largely controlled by hearing people and run as charitable institutions. Breda Carty comprehensively documents the growth of the Australian Deaf community and Australian Deaf organizations for the first time. She focuses on both the political developments of the early 20th century and on the nature of the relationships between deaf and hearing people. During this time, deaf Australians aspired to manage thier own affairs. They enjoyed some success by establishing "breakaways" from the Deaf Societies, and they also established an independent national organization, which was contested and ultimately suppressed by the Deaf Societies. These developments were influenced by wider social movements in Australian society, such as the mobilization of minority groups in their push for autonomy and equal rights. Although most of the breakaway Deaf organizations did not survive beyond the 1930s, they significantly affected the power structures and relationships between deaf and hearing people in Australia. The Australian Deaf community's attempts to organize independently during these years have been largely erased from collective memory, making Carty's examination a particularly important and necessary addition tot he historical literature. Book jacket.